Redesain Auditorium Gedung Kesenian Societeit de Harmonie (GKSdH) Sulawesi Selatan dengan Pendekatan Partisipatif - Ishak, Rahmi Amin; Martosenjoyo, Triyatni; Beddu, Syarif; ., Dahniar; Syam, Syahriana; Ishak, Muhammad Taufik; Taufik, Yusaumi Ramadhanti Fitri (Faculty of Engineering UNHAS, 2025)
The Societeit de Harmonie Arts Building (GKSdH) is located on Jalan Riburane, Makassar City, South Sulawesi. The building was built in 1896 by the Dutch colonial government, and has undergone several renovations until 1999. For the performing arts community, the interior performance of GKSdH is considered inadequate and less representative as an art building, even though with limited funds from the Makassar City government, various renovate and procurement of building equipment gradually from year to year have been carried out by the management. The lack of maintenance and minimal operational costs of the building indicates a lack of interest in visitors and the art community to come and do activities in this building. This community service activity aims to provide the interior design of the GKSdH Auditorium, which is representative of the performing arts community. Through a participatory approach to redesign, it can be known that user preferences in meeting space needs in accordance with artistic activities in Makassar City. The results of this service activity, in addition to contributing to the idea of an auditorium interior design idea that has better performance and according to user needs, also show an increase in understanding and participation of partners; Pre-test 60,5 and Post-test 95 (out of a total score of 100), especially at the conceptual stage of redesign ideas, and awareness of building maintenance.